2018
DOI: 10.1021/acsenergylett.8b02470
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Magnesium Dendrites during Electrodeposition

Abstract: We demonstrate the growth of dendritic magnesium deposits with fractal morphologies exhibiting shear moduli in excess of values for polymeric separators upon the galvanostatic electrodeposition of metallic Mg from Grignard reagents in symmetric Mg–Mg cells. Dendritic growth is understood on the basis of the competing influences of reaction rate, electrolyte transport rate, and self-diffusion barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
206
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 16 publications
(25 reference statements)
4
206
0
Order By: Relevance
“…As a potential candidate, rechargeable Mg batteries have attracted special interest due to the unique advantages of metallic Mg anode, including low cost, high natural abundance, and high capacity (2205 mAh g −1 and 3833 mAh cm −3 ) . More significantly, except for some special cases, Mg dendrite is not easy to form during electrochemical deposition, which essentially ensures high safety for large‐scale applications . In addition, the use of metallic Mg anode widens the potential options of cathode materials, because Mg‐deficient cathode materials could be used in rechargeable Mg batteries.…”
Section: Introductionmentioning
confidence: 99%
“…As a potential candidate, rechargeable Mg batteries have attracted special interest due to the unique advantages of metallic Mg anode, including low cost, high natural abundance, and high capacity (2205 mAh g −1 and 3833 mAh cm −3 ) . More significantly, except for some special cases, Mg dendrite is not easy to form during electrochemical deposition, which essentially ensures high safety for large‐scale applications . In addition, the use of metallic Mg anode widens the potential options of cathode materials, because Mg‐deficient cathode materials could be used in rechargeable Mg batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The question that matters is “how high can the current be raised before triggering magnesium dendrite growth in a particular electrolyte?” Several publications have demonstrated that magnesium dendrites can and do grow in magnesium batteries, including one of the first seminal papers on magnesium batteries in 1990 by Gregory et al that clearly states the observation of dendritic magnesium deposits. [ 20,33–35 ] As shown in Figure a,b, Davidson et al demonstrated magnesium dendrite growth at 0.921 mA cm −2 in a 0.5 m methylmagnesium chloride solution in THF and Ding et al showed that magnesium dendrites form in symmetric cells cycled at 0.1 mA cm −2 with 1 h half‐cycles when using 0.3 m magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI) 2 ) in mono‐, di‐, and triglyme. [ 34,35 ]…”
Section: Magesium Metal Negative Electrodesmentioning
confidence: 99%
“…[ 20,33–35 ] As shown in Figure a,b, Davidson et al demonstrated magnesium dendrite growth at 0.921 mA cm −2 in a 0.5 m methylmagnesium chloride solution in THF and Ding et al showed that magnesium dendrites form in symmetric cells cycled at 0.1 mA cm −2 with 1 h half‐cycles when using 0.3 m magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI) 2 ) in mono‐, di‐, and triglyme. [ 34,35 ]…”
Section: Magesium Metal Negative Electrodesmentioning
confidence: 99%
“…[ 5 ] Note that the electrodeposition of Mg metal is not totally free of dendrite formation in all conditions. [ 6 ] In general, these attractive characteristics have established MIBs as one of promising electrochemical energy storage technologies for applications beyond LIBs. Consequently, initial key milestones on the way of research development of MIBs have been successfully undertaken over the last two decades.…”
Section: Introductionmentioning
confidence: 99%